A new species of ghost shrimp of the genus Michaelcallianassa Sakai, 2002 (Crustacea: Decapoda: Axiidea: Callichiridae) from subtidal waters of the Persian Gulf, Iran - Sepahvand, Vahid; Momtazi, Farzaneh; Tudge, Christopher (Zootaxa, 2020)
A third species of Michaelcallianassa Sakai, 2002 is described based on two specimens from subtidal waters of the Persian Gulf. Michaelcallianassa persica sp. nov. resembles M. indica Sakai, 2002 from the Andaman Sea, but can be differentiated by possession of six spines on the cutting edge of the large cheliped, a telson with two pairs of lateral movable spines as well as two spines dorsally in the center of the telson and an exopod with a row of spines on the postero-distal margin. The new species compares favorably with congeners M. indica Sakai, 2002 and M. sinica Liu & Liu, 2009 in many diagnostic aspects, including body shape, the relative size and shape of pereopods 2–4, maxilliped 3, and the rostrum. Some limited comparison is made to the related genus Balsscallianassa Sakai, 2011.